2009
DOI: 10.1590/s1413-70542009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Estudo anatômico de cafeeiros enxertados

Abstract: RESUMONeste trabalho, objetivou-se, avaliar as características anatômicas do caule de cafeeiros enxertados, auto-enxertados e pé-franco. Foram utilizadas as cultivares Catucaí Amarelo 2 SL e Topázio MG 1190 (Coffea arabica L.) e o porta-enxerto Apoatã IAC 2258 (C. canephora Pierre ex Froehn.). As seções anatômicas longitudinais e transversais foram realizadas aos 30, 60 e 90 dias após a enxertia. Os resultados não mostraram evidências de incompatibilidade de reconstituição e formação de tecidos entre as cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…1i). This may affect the normal plant development, since the delayed recovery of vascular tissues may affect other factors such as the translocation of water and nutrients from the rootstock to the graft and from the canopy to the rootstock (DIAS et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…1i). This may affect the normal plant development, since the delayed recovery of vascular tissues may affect other factors such as the translocation of water and nutrients from the rootstock to the graft and from the canopy to the rootstock (DIAS et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In stem grafting bud of "Valencia" orange on rootstock of "Cravo" lemon, [16] observed that there is no need of juxtaposition of the vascular tissue, with proliferation of parenchyma cells and sorting for the continuity of vascular tissues. [17] observed that, when there is an overlap of the vascular tissue, the reconstitution of the vascular system appeared to be more efficient and rapid on grafted coffee. The long period of domestication and grafting in orange is not comparable with the little knowledge we have about araticum, where there seems to be a requirement to align the cambium, such as with coffee.…”
Section: Histochemical and Anatomical Analysis Of Araticum Grafting O...mentioning
confidence: 97%